Teacher Perceptions of Moodle and Throughput in a Blended Learning Programme for In-Service Secondary School Mathematics Teachers. Issue 2 (3rd April 2018) - Ndlovu, Mdutshekelwa C.; Mostert, Ingrid
ABSTRACT: The purpose of this article is to analyse teachers' perceptions of using the modular object-oriented dynamic learning environment (Moodle) platform as a learning management system in a small-scale blended learning (b-learning) Advanced Certificate in Education (ACE) programme for in-service secondary school mathematics teachers in South Africa. It describes how the Moodle platform was used in combination with on-campus and later off-campus contact sessions for a widely dispersed population of 76 in-service mathematics teachers over a four-year period. Qualitative data was gathered by means of a questionnaire with open-ended items, while quantitative data was gathered from the centre's archives. The main findings were that Moodle enabled in-service teachers to experience social, cognitive and teaching presences, through synchronous and asynchronous discussions with peers and facilitators, and a teaching presence by submitting their inquiries and assignments online for facilitators to provide them with answers and feedback. The main obstacles to the integration of Moodle were limited availability of technology, slow speed, and unaffordable cost when available. With increased broadband connectivity Moodle holds the prospect for diversifying b-learning experiences that can support teachers' professional learning outcomes and throughput for distributed populations of practising mathematics teachers, in particular.